Initial teacher training in the promotion of positive assessment of mathematics competition: a case study - Báez Suero , M. Sc. Isidro; Legañoa Ferrá, Dra. C. María de los Ángeles; García Batán, Dr. C. Jorge (Transformación, 2024)
The paper describes the results of a case study aimed at developing the competence to promoting positive assessment of mathematics in primary school teachers under training. The objective was to evaluate the effectiveness a pedagogical strategy aimed at developing such competence during the teaching practice as organized at “Salomé Ureña” College of Education in San Juan de la Maguana province, Dominican Republic. For the case study the Yin typology was assumed, and the type of multiple cases, the embedded design was selected for evaluating the two variants of the strategy. To evaluate the effectiveness of the training, four dimensions were defined and different techniques were selected: participant observation, portfolio analysis, evaluation of teaching practice, reflective workshops, among others. The findings allowed to conclude that the performance relative to the first level of the competition was reached, as well as actions on the family and the context, corresponding to the third level for both variants.